Guanine nucleotide-binding protein Go-induced coupling of neuropeptide Y receptors to Ca2+ channels in sensory neurons. - Ewald, D A (1988)
Neuropeptide Y (NPY) inhibited the Ca2+ current (ICa) in rat dorsal root ganglion neurons in vitro. NPY inhibited the sustained ICa evoked by steps to 0 mV from a holding potential of -40 mV and the inactivating ICa, which was additionally evoked from a more negative holding potential of -80 mV. The effects of NPY on both phases of the ICa were abolished if cells were first treated with pertussis toxin (PTX). When a combination of GTP and the purified alpha-subunit of the guanine nucleotide-binding protein Go was perfused into PTX-treated cells, the inhibitory effects of NPY on the ICa reappeared in a time-dependent fashion. GTP or alpha-subunit perfused separately was relatively ineffective. The effects of NPY reappeared more rapidly at higher concentrations of alpha o. Chronic treatment of these cells with phorbol ester "down-regulates" protein kinase C (PKC) and reduces inhibition of the sustained current by NPY. In PTX-treated cells in which PKC had been removed by down-regulation, inhibition of ICa was also reconstituted following the perfusion of GTP/alpha o. Under these circumstances, NPY inhibited the transient phase of the ICa more than the sustained phase. These results indicate that Go, the major PTX substrate in the central nervous system, may normally mediate the inhibitory effects of NPY receptors on dorsal root ganglion Ca2+ channels.